The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1186/s13018-019-1136-7
|View full text |Cite
|
Sign up to set email alerts
|

Indirect 3D printing technology for the fabrication of customised β-TCP/chitosan scaffold with the shape of rabbit radial head—an in vitro study

Abstract: Background With the development of indirect three-dimensional (3D) printing technology, it is possible to customise individual scaffolds to be used in bone transplantation and regeneration. In addition, materials previously limited to the 3D printing (3DP) process due to their own characteristics can also be used well in indirect 3DP. In this study, customised β-TCP/chitosan scaffolds with the shape of rabbit radial head were produced by indirect 3D printing technology. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The manipulation of three-dimensional models seems to facilitate the diagnosis and reproducibility using the AO/OTA and Neer Classifications, 1970 [5]. In the case of surgical treatments, preoperative planning can be carried out with 3D-models, allowing the surgeon to train strategies and maneuvers to reposition the deviated bone fragments and choose the implants for each patient before surgery [11,18,19]. The choice involves size and models of plates or nails, screws, and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manipulation of three-dimensional models seems to facilitate the diagnosis and reproducibility using the AO/OTA and Neer Classifications, 1970 [5]. In the case of surgical treatments, preoperative planning can be carried out with 3D-models, allowing the surgeon to train strategies and maneuvers to reposition the deviated bone fragments and choose the implants for each patient before surgery [11,18,19]. The choice involves size and models of plates or nails, screws, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Slings, plates, nails, and prostheses are nowadays the therapeutic arsenal used to correlate the patient’s fracture with the surgeon’s skills to decide on the best treatment. Thus, research on topics involving new classifications or diagnostic methods have been presented [ 6 , 13 , 18 , 20 24 , 29 , 30 ] [ 6 , 13 , 18 , 20 24 , 29 , 30 ] and studies with 3D-models are promising [ 11 13 , 19 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may due to the osteogenic ability of the CS-b-TCP layer, as it is capable of promoting attachment and osteogenesis of BMSCs. 26 From the results of histological examination (Fig. 6c, g), the defects treated by the bi-layer scaffold were filled with the newly formed bone, whereas the defects treated by the CS scaffold were incompletely filled.…”
Section: Disscussionmentioning
confidence: 93%
“…24 To overcome the disadvantage of the inorganic ceramic material, b-TCP is often combined with other organic biopolymer materials. 25 It has been proved that scaffolds with b-TCP and CS can not only promote the adhesion and proliferation [25][26][27] but also promote the osteogenic differentiation of osteoblasts and bone marrow stem cells (BMSCs). 26,27 Therefore, the bi-layered composite scaffold with CS acted as a cartilage layer and CS-b-TCP as a bone layer was fabricated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the β-TCP-PLA mixture membrane has been demonstrated to favor bone healing in the anterior esthetic area of the maxilla in a recent clinical study (Canullo et al, 2019). It has also been revealed that β-TCPchitosan composite scaffolds can significantly enhance the proliferation and osteogenic differentiation of BMSCs in vitro (Wang et al, 2019a). Additionally, the addition of pulverized human bone into β-TCP-chitosan composite scaffolds presented excellent mechanical properties and induced significantly higher ALP activity than β-TCP-chitosan composite scaffolds when seeded with MG63 cells (Kowalczyk et al, 2021).…”
Section: Beta-tricalcium Phosphate In Combination With Other Materialsmentioning
confidence: 97%